Foreign Puppets, Christian Mothers or Revolutionary Martyrs? The Multiple Identities of Missionary School Students in Zhejiang, 1923-1949 - Bond, Jennifer (Journal of Research for Christianity in China (JRCC), 2025)
The words of Yu Zhanghua (俞彰華) published in the 1933 edition of the Yongjiang School magazine, The Riverside Echo (Yongjiang Sheng, Yongjiang nüzi zhongxue xiaokan, 甬江聲,甬江女子中學校刊) reveal both the intimate association between Nationalism and Christianity and a sense of profound responsibility to save China that Yongjiang school pupils felt in 1930’s Zhejiang province. Yongjiang School (Riverside Academy, Yongjiang nüzi zhongxue, 甬江女子中學) was an American Presbyterian and Baptist Mission school for girls, whose history can be traced back to the first mission school for girls founded in 1844 by British missionary Mary Ann Aldersey. The essays, short stories, plays and poetry of Yongjiang students published in the annual school magazines (1931, 1933, 1948), touch upon a fascinating variety of topics ranging from school daily life, personal friendships and family relations, to the status of women’s education and the urgent need for young people to become strong future leaders who could save China from national crisis. The poignant, urgent, humorous and sometimes sad voices that come to us through these magazines offer the historian a unique insight into a crucial moment in modern Chinese history.